Minthostachys verticillata essential oils as potential phytogenic additives and chemoprotective strategy on aflatoxin B1 toxicity - Escobar, Franco Matias (2019)
The aim of the current study was to evaluate the protective effects of Minthostachys verticillata essential oil (Mv-EO) against aflatoxin B1-induced toxicity in Vero cells in vitro and in male rats. The cytotoxicity of AFB1 (0-30 µg/mL) and Mv-EO (0-500 µg/mL) was determined on Vero cells using the Neutral Red assays. The tested Mv-EO did not cause genotoxicity or cytotoxicity in vivo and was able to attenuate AFB1-caused cytotoxicity and genotoxicity. Animals were divided into four groups consisting of 5 (five) rats in each group: T1 basal feed (BF – negative control), T2 BF + Mv-EO [0.04%], T3 BF + AFB1 [100 µg/kg], T4 BF + food with AFB1 [100 µg/kg] + Mv-EO [0.04%]. Tissue samples were collected at the end of treatment period for genotoxic study and histological examination. Treatment with Mv-EO alone and even combined with AFB1 showed a significant improvement in the histomorphometry of intestinal villi, without alteration of productive parameters. Also, the micronucleus test demonstrated that Mv-EO reduced AFB1-induced DNA damage on bone marrow cells of male Wistar rats. This study demonstrated that Mv-EO could be used as protective against AFB1-induced cytotoxicity and genotoxicity, and as phytogenic feed additive.